C-Terminal modification of polytheonamide B uncouples its dual functions in MCF-7 cancer cells. Issue 26 (15th March 2023) - Xue, Yun-Wei; Miura, Kensuke; Itoh, Hiroaki; Inoue, Masayuki
Abstract : Polytheonamide B is a large natural product that forms an ion channel in the plasma and lysosomal membranes. Herein, we report the uncoupling of the dual functions of polytheonamide B by synthetically incorporating a tertiary amine at the C-terminus. Abstract : Polytheonamide B (1 ) is an exceptionally large peptide that forms a transmembrane ion channel. The potent cytotoxicity of 1 against MCF-7 cancer cells originates from its two ion transport functions. Compound 1 depolarizes the plasma membrane and neutralizes acidic lysosomes. Here, we describe how we uncoupled these functions by designing and synthesizing new analogues of 1 .